Colour and Photography (Itinera, 2022)
Do black-and-white and colour photography really represent two different and complementary expressive languages? Or is one merely a mirror of the other, in that we 'see' colours even where they are apparently not present? Our brain reconstructs them even in their absence: cones and rods in the retina operate simultaneously and not alternately, and visual memories influence the decoding of shades of grey in a chromatic key.Black and white are nothing more than the two (unreachable) extremes of a continuum and are therefore fully part of our coloured world. All the various, unnamable as they are in fact indiscriminate, hues contain the so-called achromatics that delimit, both perceptually and psychologically, the space of colour and our way of relating to it.